2011
DOI: 10.1111/j.1755-5922.2011.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine Reduces Endogenous Free Fatty Acid Oxidation and Improves Myocardial Efficiency in Obese Humans

Abstract: SUMMARY Introduction:The metabolic modulator trimetazidine (TMZ) has been suggested to induce a metabolic shift from myocardial fatty acid oxidation (FAO) to glucose utilization, but this mechanism remains unproven in humans. The oxidation of plasma derived FA is commonly measured in humans, whereas the contribution of FA from triglycerides stored in the myocardium has been poorly characterized. Aims: To verify the hypothesis that TMZ induces a metabolic shift, we combined positron emission tomography (PET) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 47 publications
3
13
0
1
Order By: Relevance
“…These results are consistent with findings from Tuunanen et al (2008), whereby treatment of idiopathic dilated cardiomyopathy patients with trimetazidine caused a modest 10% decrease in myocardial fatty acid oxidation rates but a significant improvement in LV function. These authors also showed that trimetazidine inhibits endogenous TAG-derived fatty acid oxidation, consistent with the trend to increased gastrocnemius TAG content that we observed in HFD-induced obese mice treated with trimetazidine (Bucci et al, 2011). Therefore, it appears that the antianginal agent trimetazidine elicits cardioprotection in the setting of obesity without adversely affecting muscle insulin sensitivity, though a more prolonged treatment may yield different results.…”
Section: Discussionsupporting
confidence: 67%
“…These results are consistent with findings from Tuunanen et al (2008), whereby treatment of idiopathic dilated cardiomyopathy patients with trimetazidine caused a modest 10% decrease in myocardial fatty acid oxidation rates but a significant improvement in LV function. These authors also showed that trimetazidine inhibits endogenous TAG-derived fatty acid oxidation, consistent with the trend to increased gastrocnemius TAG content that we observed in HFD-induced obese mice treated with trimetazidine (Bucci et al, 2011). Therefore, it appears that the antianginal agent trimetazidine elicits cardioprotection in the setting of obesity without adversely affecting muscle insulin sensitivity, though a more prolonged treatment may yield different results.…”
Section: Discussionsupporting
confidence: 67%
“…12,13,25 It is recognized that TMZ has antioxidant effects and its role in lipid peroxidation inhibition has been well established in different organs. [26][27][28] Hauet et al 11 demonstrated, in isolated perfused pig kidneys, that addition of TMZ to the EuroCollins (EC) storage solution reduces lipid peroxidation and improves renal tubular function compared to EC solution alone. Sulikowski et al 12 demonstrated that the pretreatment of animals with TMZ markedly attenuated renal dysfunction, morphological alterations and restored the depleted renal antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…TMZ is a clinically effective anti-ischemic agent that shifts myocardial metabolism from fatty acid oxidation to more oxygen-efficient glucose oxidation pathways, thus reducing ischemia without any hemodynamic effects [22,23]. The beneficial effects of TMZ on mortality, hospitalization and left ventricular function in ischemic heart disease have been confirmed by clinical [24,25] and animal studies [13,14]; however, the underlying molecular mechanisms of cardioprotective effects of TMZ remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%